AKTIVITAS ANTIOKSIDAN DAN SPF SEDIAAN KRIM TABIR SURYA DARI EKSTRAK ETANOL 70% KULIT BUAH PISANG AMBON (Musa acuminata Colla) - Herson Cahaya Himawan; Eem Masaenah; Veronika Cahyandari Eko Putri (Sekolah Tinggi Teknologi Industri dan Farmasi Bogor, 2018)
Ambon banana peel contains antioxidants that are used to brighten and moisturize the skin. Antioxidant can delay and prevent free radicals on the skin. The purpose of this research was to make a sunscreen cream preparation from ethanol 70% extract of ambon banana peel with good physical quality, activity of antioxidant and Sun Protection Factor (SPF) and the stability of sunscreen cream. The antioxidant activity test used the DPPH method while determining of SPF value in vitro using a UV-Vis Spectrophotometer. The results of this research indicate that extract ethanol 70% of Ambon banana peel can be made sunscreen cream that has good physical quality. Antioxidant activity ethanol 70% extract from ambon banana peel with inhibition value of 88,12 ppm, while cream preparation of formula 1 (5%) the inhibition value was 117 ppm, formula 2 (10%) the inhibition value was 107,11 ppm, and formula 3 (15%) the inhibition value was 92,04 ppm. The SPF value of ethanol 70% extract Ambon banana peel was 33,30, in cream preparation formula 1(5%) was 8,61, formula 2 (10%) was 11,65, and formula 3 (15%) was 13,72. The stability of the cream preparation is stable at 25℃.